A Theoretical & Innovative Air-Transport Policy & Analysis Conducive to Economic Growth: Incorporating Flight Scheduling, and Delay Costs - Hamzaee, Reza G. (Archives of Business Research, 2019)
The focus of this study, while incorporating other related author’s published works, is mainly on flight scheduling and various costs of delays. The intuitive concept of strong economic effects of aviation and air transport has been unexceptionally supported by the abundantly clear evidence. Hence, formulation of a dynamic and sustainable policy, based on massive evidence, is considered mandatory. Innovative policies would internalize major components of the existing positive externalities to enhance the success, efficiency, and viability of the industry, which would be conducive to economic development. Policy optimization in air transport industry could be a major ground for exploration of some innovative Integration of appropriate regulations and deregulations conducive to a tangible success in business and economic growth. This study applies an inductive method: Some already published evidence and empirically measured economic effects would lead to the formulation of an integrative economic policy framework that can be applied accordingly in the future for more empirical examinations and adoption.